Recognizing Obesity and its Complications: The Story of Score 1 for Health. (January 2015) - Hampl, Sarah; Campbell, Annette
This introductory article on the comorbidities of obesity in children is an overview and the first in a series of articles on the subject. One in three of our nation's school-age children is overweight or obese. The comorbidities they experience mirror those seen in adults, with over 60% of children having at least one complication. Virtually any body system may be affected. Complications include weight-related bullying and teasing, poor sleep hygiene, well-studied cardiovascular disease risk factors, liver disease, and musculoskeletal complications, to name a few. The article will further explore an exemplary program highlighting the important role that school nurses play in this child and adolescent health crisis.